INDEKS LAYANAN PENDIDIKAN AGAMA PADA SMA DAN SMK DI 34 IBU KOTA PROVINSI - Hayadin Ode Hayadin (Badan Litbang dan Diklat Kementerian Agama RI, 2018)
AbstractThe research aimed to find out the religious education services in schools to students based on their respective religions, as indicated by the availability of religious teachers according to the religion of the students, the availability of religious learning facilities, and the capacity of learning services organized by the teachers of religious education. The study conducted in 2016, using survey methods at 34 provincial capitals in Indonesia. The study population was senior high schools and vocational senior high schools. The sample selected by proportional random sampling technique, by calculating the representation of vocational schools and non-vocational ones, and also public and private status proportionally. The data collecting instrument used questionnaires. Technique of collecting data by using surveyor those who were supervisor at each region. They were given coached first before performed the task, and then undertaken spot check to school targeted by the researchers. The results showed that the number of religious education services nationally included in the high category, which was 7.8 point. The score was an aggregation of the availability of religious teachers, the availability of religious instructional means, and the capacity of religious teachers in serving studets on religious activities and learning in schools.Â AbstrakPenelitian ini bertujuan untuk mengetahui layanan pendidikan agama kepada siswa berdasarkan agama masing-masing, yang ditunjukan dengan indikator ketersediaan guru agama sesuai agama siswa, ketersediaan fasilitas pembelajaranagama, dan kapasitas layanan pembelajaran yang diselenggarakan oleh guru pendidikan agama. Penelitian di lakukan pada tahun 2016, menggunakan metode survei pada 34 ibu kota provinsi di Indonesia. Populasi penelitian adalah sekolah memengah atas (SMA) dan sekolah menengah Keterampilan (SMK). Pemilihan sampel dilakukan dengan teknik proportional random sampling, dengan menghitung keterwakilan SMA, SMK berstatus negeri dan swasta secara proporsional. Responden penelitian adalah pimpian sekolah atau tata usaha. Instrumen pengumpul data menggunakan kuisioner. Teknik pengumpulan data dengan menggunakan surveyor yang berstatus sebagai supervisor (pengaweas sekolah) yang berasal dari masing-masing kota. Mereka diberikan arahan (coaching) terlebih dahulu, dan dilakukan spotcheckÂ ke sekolah sasaran oleh peneliti. Hasil penelitian menunjukan bahwa angka layanan pendidikan agama secara nasional termasuk dalam kategori tinggi, yakni sebesar 7,8. Angka tersebut adalah agregat dari ketersediaan guru, ketersediaan sarana pembelajaran agama, dan kapasitas guru agama dalam melayani sisswa dalam aktivitas dan pembelajaran agama.